Labelisasi gizi pada kemasan makanan siap saji terhadap keputusan pembelian - Junaidi, Dicky; Dahlan, Kandi Sofia Senastri (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
This study examines the influence of prices and healthy food on purchasing decisions for UMKM ready-to-eat packaged food products, with information labels as a mediating factor. The data was collected through a non-probability sampling method using a google form online questionnaire, with a total of 196 respondents who had purchased UMKM packaged food in Indonesia. The study utilized Partial Least Square SEM and identified the variables Price and Healthy Eating as the dependent variables, Purchase Decision as the independent variable, and Information Label as the mediating variable. The results indicate that price and healthy food have a positive and significant effect on information labels, information labels have a positive and significant effect on purchasing decisions, healthy food has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, information labels mediate the effect of healthy food on purchasing decisions, and information labels mediate the effect of prices on purchasing decisions.